'Reflexology: Exploring the mechanism of action'. (August 2022) - Whatley, Judith; Perkins, Joanne; Samuel, Carol
Abstract: Reflexology is a complementary therapy focusing mainly on the application of pressure on the feet, hands and ears. A small but growing evidence base suggests that positive outcomes can be gained in the management and improvement of symptoms across a range of conditions. Biological plausibility is a key concept in the determination of the usefulness of therapies. Research which tests for safety and efficacy alongside the underpinning mechanism of action are therefore important. This paper explores the potential mechanism of action for the outcomes associated with reflexology treatment as reflected in the current evidence. The influences of therapeutic touch, relaxation, placebo effects and the similarities with other therapeutic methods of structural manipulation are considered. The lack of clarity around the precise definition of reflexology and the challenges of researching the therapy as a treatment tailored to individual need are discussed. A deeper understanding of the mechanism of action for reflexology may help to further develop research into safety and efficacy. Such an understanding may lead to the integration of knowledge which may provide both symptomatic support and longer term preventative health benefits.